Sudden bio-mathematical self-similarity and the uniqueness of human mass societies: from T-patterns and T-strings to T-societies - Magnusson, Magnus S. (Frontiers in Psychology, 2023)
With the explosive growth of human knowledge and especially in the 20th century with even greater facilitation of access to knowledge, the world of even relatively recent great thinkers becomes daunting seen from a modern viewpoint. Recently humans ignored the existence of the complex intracellular world of cell organs, giant information molecules, and societies of specialized worker molecules, nor generally about the surprising nanoscale world visible to humanity for a few decades. Sudden insights, computational power, and video technology were inaccessible to all scientists from, for example, Aristotle to Freud, so new views and ideas seem to be expected about phenomena at all scales including nano and human. Some have arrived very recently. So even urgently needed knowledge about the biology of animal and human behavior thus received the first Nobel Prize as late as 1973, in Physiology and Medicine, shared by Karl von Frisch, Konrad Lorenz, and Niko Tinbergen. Lorenz’s Nobel lecture was entitled “Analogy as a Source of Knowledge” but did not mention such self-analogy (self-similarity) as the nanoscale phenomena at the heart of this paper had barely become available. The views and empirical findings presented in this paper depend on such new intracellular nanoscale insights and computational power and have grown out of among others the development and application of mathematical models and algorithms for the analysis of structure in observable behavior and eventually in molecules such as DNA and proteins and in texts. This led to the realization of biologically sudden and unique structural/mathematical similarities (analogies) between protein and human mass-social phenomena; here between first and second-order T-societies of the first-order in proteins and of second-order only in modern literate humans. The trajectory to this view has been through the definition and detection of T-patterns and T-strings (strings with T-patterns) and then T-string-based T-societies, realizing the similarities between those in proteins and humans, and the biologically sudden and unique self-similarity found only in second-order T-societies, that is, T-societies of T-societies, only found in text-based human mass societies and appearing only a biological eye-blink ago with the advent of such precise external memory as written language, texts.